Оцінка модуля неперервності кватерніонного сингулярного інтеграла Коші - Герус, О.Ф. (Український математичний журнал, 2010)
Установлена верхняя оценка модуля непрерывности кватериионного сингулярного интеграла Коши через модуль непрерывности подынтегральной функции и метрическую харак теристику кривой. We establish an upper bound for the modulus of continuity of a quaternion singular Cauchy integral in terms of the modulus of continuity of the integrand and a metric characteristic of a curve.